2017
DOI: 10.1002/2017rs006295
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GPS Multifrequency Signal Characteristics During Periods of Ionospheric Scintillations from an Anomaly Crest Location

Abstract: Multifrequency GPS transmissions have provided the opportunity for testing the applicability of the principle of frequency diversity for scintillation mitigation. Published results addressing this issue with quantified estimates are not available in literature, at least from the anomaly crest location of the Indian longitude sector. Multifrequency scattering within the same L band is often the attributed cause behind simultaneous decorrelated signal fluctuations. The present paper aims to provide proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Delay et al () have previously reported the probability distribution of interrupted tracking of GPS L1, L2C, and L5 signals in terms of scintillation‐induced data gap as a function of S 4 from a station near Brazil, thereby suggesting less robustness of L2C and L5 compared to L1. Decorrelation of GPS triple‐frequency signals, in terms of S 4 and C/N O , during periods of ionospheric scintillations, have been studied by Goswami et al () from Calcutta. Carrano et al () have also emphasized the use of frequency diversity to mitigate the effects of scintillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delay et al () have previously reported the probability distribution of interrupted tracking of GPS L1, L2C, and L5 signals in terms of scintillation‐induced data gap as a function of S 4 from a station near Brazil, thereby suggesting less robustness of L2C and L5 compared to L1. Decorrelation of GPS triple‐frequency signals, in terms of S 4 and C/N O , during periods of ionospheric scintillations, have been studied by Goswami et al () from Calcutta. Carrano et al () have also emphasized the use of frequency diversity to mitigate the effects of scintillation.…”
Section: Discussionmentioning
confidence: 99%
“…Vilà‐Valls et al () have presented a new model‐based method to achieve a solution toward mitigation challenges posed by scintillation‐corrupted measurements. Suggested techniques for improvement of satellite signal reception capability may apply the principles of spatial diversity of different satellite constellations (Paul et al, ), frequency diversity between different frequencies of GNSS satellite links (Goswami et al, ) and interoperability between different satellite‐based navigation systems (Goswami et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…• Statistical characteristics of VHF scintillation and drift have been examined for quiet/disturbed periods during 2015-2017 over China sea • Seasonal asymmetry in the occurrence of scintillation was observed in 2015-2016 but no such asymmetry was apparent in 2017 (low solar) • Disturbed period irregularity drift during moderate geomagnetic storm of 08 September 2017 indicated >200% deviation w.r.t. quiet period important constituent of space research aimed at improving the reliability and integrity of the satellite-based navigation (e.g., Goswami et al, 2017;Sridharan et al, 2015). Owing to the increasing dependence of the mankind on the satellite-based navigation, ionospheric irregularities continue to be extensively studied even after several decades of extensive research on this topic.…”
Section: 1029/2018rs006722mentioning
confidence: 99%
“…They have achieved remarkable successes in their efforts including its real‐time assessment; however, an operational grade model to forecast the day‐to‐day variability in ionospheric scintillation still requires additional investigations to better understand the generation mechanism of intermediate‐scale irregularities. Thus, investigations to understand the background conditions under which these ionospheric irregularities are generated, remains an important constituent of space research aimed at improving the reliability and integrity of the satellite‐based navigation (e.g., Goswami et al, ; Paul & Paul, ; Sridharan et al, ). Owing to the increasing dependence of the mankind on the satellite‐based navigation, ionospheric irregularities continue to be extensively studied even after several decades of extensive research on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Global Navigation Satellite System (GNSS) provides collectively worldwide positioning, navigation, and timing determination capability using one or more satellite constellations. The reception of multiconstellation satellite signal can enhance the performance of satellite‐based navigation system under conditions of intense ionospheric scintillations as experienced during equinoctial months of high sunspot number years at equatorial locations through application of the principles of spatial diversity (Paul et al, ), frequency diversity (Goswami et al, ), and interoperability. Presently, GPS, GLONASS, GALILEO, and Beidou/COMPASS are the operational GNSS.…”
Section: Introductionmentioning
confidence: 99%